Mechanisms of General Anesthesia - Hansen, Scott B (Annual review of biochemistry, 2025)
Anesthetics are a chemically diverse collection of molecules that dictate neuronal excitability and form the basis of modern medicine. Their molecular mechanism of action is fundamental to understanding nerve excitability, mood, consciousness, and psychiatric disease. Sites of anesthetic action are located within ion channels and the plasma membrane. In the membrane, palmitate, a 16-carbon lipid, covalently links proteins and binds a lipid site to allow anesthetic sensitivity. In ion channels, anesthetics bind within an allosteric conduction pathway or compete for binding of regulatory lipids. Mechanisms of action arising from these binding sites share structural and functional characteristics with the classic anesthetic site in the enzyme luciferase. An update on the Meyer–Overton correlation is reviewed relative to each mechanism and placed in historical context with early theories. The review ends with a discussion of unresolved questions, including questions concerning endogenous anesthetics, anesthetic stereoselectivity, and aspects of a chain-length cutoff.